Protecting Women from Cancer by Giving HPV-Vaccine - Padma, K (Journal of Biomedical and Pharmaceutical Research, 2022)
Role of women in human life in various stage are as a mother , wife, sister, sister –in-law, mother- in – law, daughter, daughter-in- law friend saving her life protecting her life from any type of cancer, can save a whole familyKeywords: WHO, HPV